Comparison of DECAF score and DECAF+Lactate score in the prediction of mortality in patients with acute exacerbation of COPD - Tanrikulu, Gulcan; Guven, Ramazan; Korkut, Semih; Kalafat, Utku Murat; Duz, Dilan; Avci, Akkan; Dogan, Serkan (Vojnosanitetski pregled, 2024)
Background/Aim. Chronic obstructive pulmonary disease (COPD) is a chronic process that progresses with exacerbations. Various studies are carried out to predict mortality. Among the routine tests used to monitor and treat disease in the emergency department, special efforts are made to find those that are meaningful and diagnostic. The aim of the study was to compare the DECAF score and DECAF+Lactate score and examine the significance of the DECAF+Lactate score in predicting mortality in critically ill patients presenting with COPD exacerbation. Methods. This prospective multicentric study included 435 patients recruited from two centers. Patients who presented to the emergency department with acute COPD exacerbation and fit the definition of critically ill according to the quick Sequential Organ Failure Assessment (qSOFA) were included in the study. The prognostic values of the scores were compared using the receiver operating characteristic (ROC) curve analysis. The efficiency of scoring 28-day mortality was compared with logistic regression analysis. Results. For 435 patients, sensitivity, specificity, and area under the curve (AUC) were calculated for lactate, DECAF score, and DECAF+Lactate score, which were statistically significant in the ROC curve analysis for predicting mortality: 50%, 90.2%, 0.711, odds ratio (OR): 0.622 [95% confidence interval (CI): 1.573–2.203]; 57.6%, 64.3%, 0.654, OR: 0.618 (95%CI: 1.501–2.291); 60.1%, 75.4%, 0.744, OR: 0.790 (95%CI: 1.826–2.659), respectively. Each unit increase in the DECAF+Lactate score increased the risk of mortality by 2.203. Conclusion. As a result of our study, we believe that the DECAF+Lactate score is a more effective scoring system than the DECAF score as a predictor of mortality in critically ill patients with COPD exacerbation.
Keywords: critical illness; lactates; mortality; prognosis; pulmonary disease, chronic obstructive; sensitivity and specificity; severity of illness index